IMPLEMENTATION OF THE BAN ON THE USE OF FISHING GEAR WHAT IS NOT ALLOWED BASED ON FISHERIES LAW CASE STUDY: JURU BANU VILLAGE - Vanesya Chrismatiur Pasaribu; H.Suriansyah Murhaini; Yurika Fahliany Dewi; Aris Toteles (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The use of prohibited fishing gear is still frequently found in various Indonesian waters and has a negative impact on the sustainability of fishery resources and violates the provisions of the Fisheries Law. This study aims to analyze the implementation of the ban on the use of prohibited fishing gear by related parties and examine the obstacles faced in its implementation. The research method used is empirical legal research with a field approach through interviews. The results of the study indicate that the implementation of the ban has been carried out by law enforcement officers and related agencies through supervision, enforcement, and socialization to fishing communities. However, in its implementation, various obstacles remain, including low public legal awareness, limited supervisory facilities and infrastructure, and economic factors that encourage fishermen to continue using prohibited fishing gear. Therefore, increased coordination between related parties and ongoing educational efforts are needed to increase the effectiveness of the ban's implementation and protect the sustainability of fishery resources.